Identifying NOx Hotspots in Transient Urban Driving of Two Diesel Buses and a Diesel Car - Felix C. P. Leach; Mark S. Peckham; Matthew J. Hammond (Atmosphere, 2020)
NOx emissions from vehicles have been a substantial cause for concern due to their impact on urban air quality. In particular, despite reducing levels of permitted emissions legislatively, such reductions have not been observed in the real world. In this work, NOx emissions from three vehicles—a Euro 5 car, a Euro V hybrid bus, and a Euro VI—bus have been measured in real driving conditions (and in the case of the buses—in full passenger service). A recently developed high spatio-temporal resolution technique combining very fast (10 ms) NOx measurement with differential GPS accurate to 1 cm allows these emissions to be resolved to a distance of less than 10 cm (worst-case—dependent on vehicle speed). The results show that acceleration events for the vehicles play a significant part in their total NOx emissions. In addition, standard events such as a speed bump and a bus stop are analysed. The temperature of any aftertreatment (catalytic converter) to reduce NOx emissions is also observed to be of substantial significance. At idle, the passenger car was observed to near-double its NOx emissions when the air conditioning was switched on. Finally, the real driving conditions are compared to the legislative compliance cycles for the certification of the buses, and those results used to further understand the observed NOx emissions.